Information Sharing through Twitter by Public Health care Institution during COVID-19 Pandemic: A Case Study of AIIMS, Raipur - Sharma, Shiv Shankar; Kaur, Daljeet; Chawla, Taranjeet Kaur; Kapoor, Vaishali (Indian Journal of Community Health, 2021)
Background: During the time of COVID 19, public health care institutions have used social media to inform and aware society. Aim & Objective: To analyze how Public Health Care Institutes conveyed the health information and messages through social media platform- Twitter during COVID 19, and analyzing its impact through sentiment analysis of comments. Material & Methods: The Thematic and sentiment analysis method has been used to analyze the data of the Twitter handle of AIIMS, Raipur in two phases; January-March 2020, and April-June 2020. Results: The analysis shows that the sharing of COVID-19 updates on AIIMS, Raipur Twitter handle increased the followers 15 times from 2,000+ in March 2020 to 30,000+ in June 2020, and the sentiment analysis reflects that COVID related updates received 96.7 % positive comments. Conclusion: The case study finds that transparent and informative message sharing through social media by public health care institutions can create an effective channel of communication. This results in a positive institutional image.